The Influence of Financial Literacy and Financial Inclusion on MSME Financial Performance in Makassar City - Amry Mahdan Abrari (Economics and Business Journal (ECBIS), 2023)
This study aims to examine and analyze the effect of financial literacy and financial inclusion on the financial performance of MSMEs in Makassar City. Sources of data in this study are primary data and secondary data. The population is all MSMEs in Makassar City which are registered with the Makassar City Cooperatives and MSMEs Office with sample selection using certain considerations (purposive sampling). The analytical method used is multiple linear regression analysis with SPSS (Statistical Product and Service Solutions) tools.